2020
DOI: 10.11591/ijpeds.v11.i2.pp1082-1087
|View full text |Cite
|
Sign up to set email alerts
|

An improved control for MPPT based on FL-PSo to minimize oscillation in photovoltaic system

Abstract: Photovoltaic (PV) is a source of electrical energy derived from solar energy and has a poor level of efficiency. This efficiency is influenced by PV condition, weather, and equipments like Maximum Power Point Tracking (MPPT). MPPT control is widely used to improve PV efficiency because MPPT can produce optimal power in various weather conditions. In this paper, MPPT control is performed using the Fuzzy Logic-Particle Swarm Optimization (FL-PSO) method. This FL-PSO is used to get the Maximum Power Point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…To reduce pollutant emissions. [25], [26] Solar Low Total Harmonic Distortion, zero ripple output To improve power generation [27] Solar To reduce power oscillation and increase PV efficiency To attain the maximum power point is very less [28], [29] Solar and Wind…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce pollutant emissions. [25], [26] Solar Low Total Harmonic Distortion, zero ripple output To improve power generation [27] Solar To reduce power oscillation and increase PV efficiency To attain the maximum power point is very less [28], [29] Solar and Wind…”
Section: Discussionmentioning
confidence: 99%
“…Logeswaran et al [26] have discussed about the solar system in presence of MPPT and BAT optimization it will provide more efficiency. Firdaus et al [27] have purposed the PV source with MPPT technique to increase PV efficiency by integrating fuzzy logic PSO (FL-PSO) method. Kaur and Bala [28] have purposed the concept different technology included for analyzing optimal location and capacity of DG units.…”
Section: Renewable Sources With Optimization Algorithmsmentioning
confidence: 99%
“…PSO is a meta-heuristic algorithm that draws inspiration from migrating bird behaviour. We attribute the construction of artificial intelligence [29]. The ( 9) and (10) show the standard formulations of PSO commonly used.…”
Section: − Using Pso Algorithm For Scaling βmentioning
confidence: 99%
“…Mohanty et al devised the grey wolf optimization in order to gather the greatest amount of electricity from the PV systems while they were partially shaded. The findings of the simulation are analyzed and contrasted with those of the P&O and enhanced particle swarm optimization (PSO) methods [3], [6], [14], [26], [34], [70], [212], [214], [253], [254]. The results of the tests demonstrated that the grey wolf optimization works better than traditional algorithms in terms of tracking speed, ripple content, and extraction efficiency [255].…”
Section: Maximum Power Point Tracking (Mppt)mentioning
confidence: 99%